2016
DOI: 10.1186/s40880-016-0120-4
|View full text |Cite
|
Sign up to set email alerts
|

Palliative primary tumor resection provides survival benefits for the patients with metastatic colorectal cancer and low circulating levels of dehydrogenase and carcinoembryonic antigen

Abstract: BackgroundIt remains controversial whether palliative primary tumor resection (PPTR) can provide survival benefits to the patients with metastatic colorectal cancer (mCRC) who have unresectable metastases. The aim of this study was to evaluate whether PPTR could improve the survival of patients with mCRC.MethodsWe conducted a retrospective study on consecutive mCRC patients with unresectable metastases who were diagnosed at Sun Yat-sen University Cancer Center in Guangzhou, Guangdong, China, between January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Figure 1 shows the study flow diagram. Seventy‐seven comparative studies fulfilled the inclusion criteria of this meta‐analysis [2, 4–8, 10–27, 30–50, 69–100]. There were 159,991 patients for analysis, including 94,745 (59.2%) in the PTR group and 65,246 (40.8%) in the PTI group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the study flow diagram. Seventy‐seven comparative studies fulfilled the inclusion criteria of this meta‐analysis [2, 4–8, 10–27, 30–50, 69–100]. There were 159,991 patients for analysis, including 94,745 (59.2%) in the PTR group and 65,246 (40.8%) in the PTI group.…”
Section: Resultsmentioning
confidence: 99%
“…For patients with incurable colorectal cancer, an important question which remains unanswered to date is whether the best treatment strategy is primary tumor resection (PTR) with chemotherapy or immediate chemotherapy without PTR. Previous published comparative studies reported conflicting results on this issue, with some studies demonstrating improved survival with PTR compared to primary tumor intact (PTI) [2, 4–32], while other studies found no significant differences between the two groups [33–40], and other studies suggested systemic chemotherapy without resection of the primary tumor is the treatment strategy of choice for patients with incurable colorectal cancer [41–50]. The purpose of the present study was to perform a systematic review of the literature and employ meta‐analytical techniques to compare survival and adverse events in patients undergoing PTR versus PTI, with or without chemotherapy, in order to determine whether PTR should be performed in patients with incurable localized or metastatic colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of systemic chemotherapy and the treatment of local lesions, the benefit of palliative resection of the primary tumor in specific patient populations has been gradually recognized 19, 20. In our previous study, we found that patients with normal lactic dehydrogenase levels and a CEA level <70 ng/mL could benefit from palliative operation surgery without serious surgery-related complications 8.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that certain populations can benefit from palliative resection 5-7. In our previous study, we found that palliative resection improved overall survival (OS) and progression-free survival (PFS) in certain patients 8.…”
Section: Introductionmentioning
confidence: 99%
“…48 Foi analisado um estudo de 2017, viabilidade de Infusão Arterial Hepática versus quimioterapia sistêmica, relacionando com o efeito protetor contra metástases hepáticas após ressecção curativa, em pacientes diagnosticados com câncer colorretal, que chegou a conclusão que A infusão intra-hepática não contribuiu para qualquer melhora acentuada na sobrevida global. 25 Por meio de uma análise multivariada, para pacientes com câncer colorretal metastático que possuem metástases irressecáveis, a ressecção paliativa do tumor primário pode melhorar a sobrevida geral e a progressão de sobrevida livre de progressão após a quimioterapia de primeira linha e ainda diminuir a incidência de envolvimento de novos órgãos, 28,29 dado questionado por Kim et al em seu estudo, no qual afirmou que as evidências na comparação entre a quimioterapia isolada e a quimioterapia associada à cirurgia permanecem obscuras. 49 O estudo sobre a relevância da localização do tumor primário em pacientes com câncer colorretal metastático, associada à redução inicial do tumor com o tratamento quimioterápico de primeira linha a base de FOLFIRI (irinotecano) + Panitumumabe apresentou que a redução precoce do tumor foi associada à melhora da sobrevida livre de progressão.…”
Section: Discussionunclassified